Kajian Atas Perbandingan Penyusutan Aktiva Tetap Menurut Akuntansi (Komersial) Dan Menurut Ketentuan Peraturan Perundang-Undangan Perpajakan - ., Suparman (Jurnal Akuntansi, 2014)
The Existence Of Different Concepts, Measurements, Methods, And The Recognition Of Income And Expenses Between Accounting And Taxation Lead To Differences Between Accounting Income To Taxable Income.